Nutrient Displacement Associated with Replacing Intake of Usual Snacks with Pecans: An Exploratory Analysis of a Randomized Controlled Trial - Tricia L Hart; Penny M Kris-Etherton; Kristina S Petersen (Current Developments in Nutrition)
Background: The effect of instructions to replace usual snacks with nuts on nutrient displacement is unknown. Objectives: This analysis aimed to investigate nutrient displacement and changes in food pattern component intake that occur with instructions to consume 57 g/d of pecans in place of usual snacks in adults at increased risk of cardiometabolic diseases after 6 wk and 12 wk. Methods: Data from a 12-wk randomized controlled trial were used for this exploratory analysis. Adults at risk of cardiometabolic diseases were provided with 57 g/d of pecans and instructed to replace habitually consumed snacks with the provided pecans. The control group was instructed to continue consuming their usual diet. Participants completed 3 24-h recalls at baseline, week 6, and week 12 for assessment of nutrient and food pattern component intake. Nutrient displacement was calculated according to a previously described method to estimate the extent to which nutrients provided by pecans displaced nutrients from other foods. Results: At 12-wk, partial nutrient displacement occurred for energy (84%; 331 ± 47.8 kcal), total fat (55%; 22.6 ± 0.50 g), monounsaturated fat (47%; 10.9 ± 0.23 g), polyunsaturated fat (46%; 5.71 ± 0.07 g), and fiber (60%; 3.29 ± 0.03 g) in the pecan group. Nutrient displacement >100% was observed for carbohydrates (343%; 27.1 ± 0.12 g), and full displacement of saturated fat occurred at week 12 in the pecan group. In the pecan group, intake of nuts and seeds [mean difference 2.3 oz-eq; 95% confidence interval (CI): 1.0, 3.6], oils (19.2 g; 95% CI: 12.6, 25.7), and total protein foods (2.3 oz-eq; 95% CI: 1.0, 3.6) increased. No other differences in food pattern components were observed. Results at week 6 were relatively consistent with those observed at 12-wk. Conclusions: Instructions to replace usual snacks with pecans resulted in the partial displacement of energy, total fat, unsaturated fats, and fiber. Additionally, pecan consumption increased intakes of food pattern components emphasized in healthy dietary patterns.This trial is registered at clinicaltrials.gov as NCT05071807.